Effects of Seed Pelleting on Seed Quality of Cowpea (Vigna unguiculata L.) During Storage - Singh, Nirmal; Thakur, Ashok K.; Kaushal, Rajesh; Mehta, D. K.; Bhardwaj, Ramesh K. (International Journal of Economic Plants, 2018)
An experiment was conducted during 2015-2016, to study the effects of seed pelleting on seed quality parameters of cowpea variety Himachal Lobia-1 during a storage period of one year. Seeds were checked for quality parameters at a monthly interval. Two formulations of Rhizobium viz-a-vis powder and liquid along with control (unpelleted) were used for experiment. The analysis of variance revealed that there were significant effects of seed pelleting and storage periods on germination, seedling length, seedling dry weight, seed vigour index-I and seed vigour index-II. Seeds pelleted with liquid formulation of Rhizobium gave maximum germination (93.55%) whereas unpelleted seeds gave minimum germination (91.45%) when seeds were germinated using between the paper methods. However, the germination decreased as the storage period increased. It ranged from 94.42% germination at 0 month to 89.52% at 12 months of storage. The interaction effects on germination due to seed pelleting and storage periods were found to be non-significant at 5% level of significance. Seed vigour index I was found to be maximum (2980.48) when fresh seeds were pelleted with liquid Rhizobium and minimum (2315.58) in unpelleted seeds stored for 12 months. Seed vigour index II also followed the same trend. It was found to be maximum (7451.34) in fresh seeds pelleted with liquid Rhizobium and minimum (6310.23) in unpelleted seeds stored for 12 months.